2022
DOI: 10.1001/jamaneurol.2022.3832
|View full text |Cite
|
Sign up to set email alerts
|

Association of Vascular Risk Factors and Genetic Factors With Penetrance of Variants Causing Monogenic Stroke

Abstract: ImportanceIt is uncertain whether typical variants causing monogenic stroke are associated with cerebrovascular disease in the general population and why the phenotype of these variants varies so widely.ObjectiveTo determine the frequency of pathogenic variants in the 3 most common monogenic cerebral small vessel diseases (cSVD) and their associations with prevalent and incident stroke and dementia.Design, Setting, and ParticipantsThis cohort study is a multicenter population-based study of data from UK Bioban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 39 publications
2
17
1
Order By: Relevance
“…Some studies identify differences in penetrance, expressivity, and a globally increased risk of stroke and/or vascular dementia . Cho et al reported consistent findings: pathogenic variants in all 3 genes were markedly more frequent than expected based on prevalence of clinical disease phenotypes thought to be caused by these variants. This was most notable in NOTCH3 where 1 in 467 patients were heterozygous variant carriers vs the estimated prevalence of CADASIL (4:100 000) yielding a more than 50-fold difference.…”
supporting
confidence: 87%
See 2 more Smart Citations
“…Some studies identify differences in penetrance, expressivity, and a globally increased risk of stroke and/or vascular dementia . Cho et al reported consistent findings: pathogenic variants in all 3 genes were markedly more frequent than expected based on prevalence of clinical disease phenotypes thought to be caused by these variants. This was most notable in NOTCH3 where 1 in 467 patients were heterozygous variant carriers vs the estimated prevalence of CADASIL (4:100 000) yielding a more than 50-fold difference.…”
supporting
confidence: 87%
“…In this issue of JAMA Neurology , Cho et al evaluate key questions of penetrance, expressivity, and modulation of monogenic stroke in a methodologically rigorous study of 454 756 UK Biobank participants with whole-exome sequencing data. They focus on pathogenic variants in the 3 most common monogenic cerebral small-vessel diseases (cSVDs): NOTCH3 , HTRA1 , and COL4A1/2 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…37 However, addressing vascular risk factors for sporadic vascular disease may delay onset, modify severity, or prolong the course for individuals with CADASIL and other inherited CSVDs. 25 Thus, securing a diagnosis may prove important for clinical practice and research.…”
Section: Diagnostic Approach To Cadasil and Other Genetic Csvdsmentioning
confidence: 99%
“…Recent research by Cho et al highlighted an increased risk of stroke and dementia in variant carriers of monogenic stroke genes. 4 Therefore, genetic screening using stroke gene panels could offer fresh insights for risk factor management beyond conventional vascular risk factors.We are truly impressed by the comprehensive work conducted by Härtl et al, which detected monogenic diseases in 2.9% of patients and genetic risk factors in additional 2.9% of patients. 5 This precision in genetic classification and risk assessment is invaluable.…”
mentioning
confidence: 99%